Dissection of the Trigeminal Ganglion of Nonrodent Species Used in Toxicology Studies. (January 2020) - Howroyd, Paul C.
The ganglion of the trigeminal (V cranial) nerve is generally sampled at necropsy in nonrodent toxicology studies only when somatic or autonomic peripheral nervous system toxicity is suspected. The ganglion is far more difficult to locate in nonrodents than in rats and mice, and suitable methods to dissect it have been described only for swine. The trigeminal nerve caudal to the ganglion passes through a canal, roofed by bone in dogs and rabbits and by a tough layer of dura mater in swine and nonhuman primates. The ganglion is partly or wholly obscured by overlying dura mater. Of the 3 intracranial branches of the nerve, the ophthalmic is delicate and the maxillary and mandibular have extremely short courses within the cranial cavity. Methods that are practical in routine toxicologic pathology for the dissection of the ganglion in nonrodent laboratory species are illustrated and relevant species differences in the anatomy of the intracranial part of the trigeminal nerve are highlighted.